A model-based control scheme for depth of hypnosis in anesthesia - Merigo, L.; Padula, Fabrizio; Pawlowski, A.; Dormido, S.; Guzmán Sánchez, J.; Latronico, N.; Paltenghi, M.; Visioli, A. (2018)
© 2018 Elsevier Ltd. In this paper we propose a model-based scheme to control the depth of hypnosis in anesthesia that uses the BIS signal as controlled variable. In particular, the control scheme exploits the propofol pharmacokinetics/pharmacodynamics model of the patient so that the estimated effect-site concentration is used as a feedback signal for a standard PID controller, which compensates for the model uncertainties. The tuning of the parameters is performed off-line using genetic algorithms to minimize a performance index over a given data set of patients. The effectiveness of the proposed method is verified by means of a Monte Carlo method that takes into account both the intra-patient and inter-patient variability. In general, we obtain a fast induction phase with limited overshoot and a good disturbance rejection during maintenance of anesthesia.